2007
DOI: 10.1002/jor.20474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osteogenic protein‐1 on the matrix metabolism of bovine tendon cells

Abstract: Tendon rupture is a common sports injury in adults. However, the mechanical properties of repair tissue are inferior to those of normal tissue. To accelerate tendon healing, an in vivo approach using growth factors has been applied and has shown evidence for the efficacy of biological stimulation of the repair process. Recombinant human osteogenic protein-1 (rhOP-1) has been shown to be effective in stimulating matrix production by various connective tissues. To test the effect of rhOP-1 on the matrix metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
2
17
1
Order By: Relevance
“…The current results show that BMP-7 stimulated moderately the proliferation of Achilles and Patellar cells. By comparison, a recent study also showed that OP-1 (BMP-7) stimulated cell proliferation, DNA content, synthesis of collagen and proteoglycans in bovine tendon cell cultures [Yamada et al, 2008]. BMP-2, which was previously shown to enhance tendon healing in vivo, did not stimulate proliferation of two clonal Achilles tendon cell lines [Salingcarnboriboon et al, 2003].…”
Section: Effects Of Bmp-7 On Achilles and Patellar Tendon Cell Prolifmentioning
confidence: 93%
“…The current results show that BMP-7 stimulated moderately the proliferation of Achilles and Patellar cells. By comparison, a recent study also showed that OP-1 (BMP-7) stimulated cell proliferation, DNA content, synthesis of collagen and proteoglycans in bovine tendon cell cultures [Yamada et al, 2008]. BMP-2, which was previously shown to enhance tendon healing in vivo, did not stimulate proliferation of two clonal Achilles tendon cell lines [Salingcarnboriboon et al, 2003].…”
Section: Effects Of Bmp-7 On Achilles and Patellar Tendon Cell Prolifmentioning
confidence: 93%
“…BMP7 triggers the production of fibrous tissue between tendon and bone comparable with native regeneration processes in the tissue-connecting area (Rodeo et al 1993;Gerber et al 1999). BMP7 also increases the proliferation and expression of tenocyte markers such as CollagenI and proteoglycans in a dose-dependent manner (Yamada et al 2008). In gene therapy studies of BMP2-overexpressing rat cells embedded in calcium alginate gels, a positive effect on tendon-bone healing has been observed in rabbits after anterior cruciate ligament reconstructions.…”
Section: Crosstalk At the Tendon-bone Interfacementioning
confidence: 96%
“…Until recently, although various neurotrophic factors were reported, nerve growth factor (NGF), glial cell-derived neurotrophic factor (GDNF), brain-derived neurotrophic factor (BDNF), and neurotrophin-3/4 (NT-3/4) were considered important molecules in these situations and decreased axonal degeneration and neuronal apoptosis [8,18,26]. Recent studies demonstrate recombinant human BMPs are capable of promoting regeneration in various tissues other than bone such as tendon or cartilage [7,31] and that they also possess neurotrophic functions, such as regulation of neuronal survival and differentiation [21,28,29].…”
Section: Introductionmentioning
confidence: 99%